(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
This article discusses two psychiatric symptoms, delusions and hallucinations, traditionally described as a characteristic of psychotic disorders based on the concept of behavior of the radical behaviorism of B. F. Skinner. The article begins with the criteria of the American Psychiatric Association, which describes these categories as positive symptoms of schizophrenia and shows their repercussions. A functionalist approaches to the behaviors of delusion and hallucination are considered in some important details. The concepts of vision and hearing conditioned facilities are discussed as a common experience. Finally, considerations are given to the implications of the effects of these types of behaviors, problems and suggestions are offered for dealing with such events in the clinical setting.